PEMETAAN KESESUAIAN HABITAT Rafflesia rochussenii Teijsm. et Binn. DI RESORT TAPOS TAMAN NASIONAL GUNUNG GEDE PANGRANGO - Amri Muhammad Saadudin; Agus Hikmat; Lilik Budi Prasetyo (Media Konservasi, 2012)
The research was carried out in Tapos Resort Mounts Gede Pangrango National Park (MGPNP). This study was aimed to identify physical factors which highly influence habitat suitability of R. rochussenii, to determine habitat suitability model and develop spatial mapp of habitat suitability area of the species. The research used physical variables of the habitat as follows : altitude, slope, LAI (Leaf Area Index) and distance from river. Spatial analysis was conducted  using ArcGIS 9.3 and Erdas Imagine 9.1 softwares, while photo analysis to determine LAI was done using Hemiview 2.1. Model weighting were determined using Principal Component Analysis. Based on the Principal Component Analysis, three principal components with characteristic vectors 1.358; 1.079 and 0.908 were obtained. Pysical habitat factors which gave significant effect on habitat suitability model were slope and altitude. The following was the model used to determine habitat suitability in Tapos Resort MGPNP :  Habitat suitability cumulative (Y) = (1.358 x Slope) + (1.079 x LAI) + (1.079 x Dintance from river) + (0.908 x Altitude). The result showed that there were 289.44 ha of high suitability habitat; 623.34 ha of medium suitability habitat and 213.75 ha of low suitability habitat. It was concluded that the habitat suitability map of R. rochussenii can be accepted with validation score of  96.26% for the high habitat suitability. Keywords:  mapping, habitat, Rafflesia rochussenii, Mounts Gede Pangrango National Park.